Peptide receptor radionuclide therapy implementation and results in a predominantly gastrointestinal neuroendocrine tumor population: A two-year experience in a nonuniversity setting. Issue 9 (4th March 2022) - Mejia, Alejandro; Vivian, Elaina; Nwogu, Christiana; Shah, Jimmy; Longoria, Raquel; Vo, Allison; Shahin, Islam; Verma, Jonathan; Bageac, Alexandru
Abstract : Abstract: Neuroendocrine tumors (NETs) are rare, but the incidence and prevalence of NETs are increasing in the United States. While surgery is the preferred treatment for NETs, it is not a viable option for metastatic disease. Lutathera ( 177 Lu-DOTATATE) is approved by the United States Food and Drug Administration and the European Medicines Agency for the treatment of gastroenteropancreatic (GEP)-NETs in adults. There is limited information on GEP-NET treatment responses to Lutathera. Our institution launched a peptide receptor radionuclide therapy (PRRT) service line using Lutathera with involvement from a multidisciplinary team and complete collaboration between hospital administration and clinical providers. A prospective registry study was also established in order to collect patient demographics and clinical data regarding the treatment of GEP primary NETs with Lutathera. Between August 2018 and July 2020, 35 GEP-NET patients were treated with Lutathera, of which 65.71% received 4 complete cycles and 25.71% received 3 cycles; 5.71% and 2.86% received 2 and 1 cycles of PRRT, respectively. Most adverse events during the course of our study were low grade using the common terminology criteria for adverse events system. Of the patients who completed all 4 cycles: 22% showed partial response to Lutathera, 44% showed stable disease, and 13% showed disease progression based on a qualitative assessment of positron emission tomography/computed tomography imaging. From our experience, Lutathera was well tolerated in patients with GEP-NET. Additional studies are needed to examine long-term clinical and patient-reported outcomes associated with GEP-NET treatment as well as financial considerations for hospitals embarking on a PRRT program.